A criança de seis e sete anos : estudos de memória, compreensão e cognição - Costa, Tatiane Milani da (2012)
Introduction: Since 2010, a new Brazilian law required the addition of an initial year in the elementary school curriculum in order to include six years-old students. This dissertation presents the description and discussion of a survey carried out during the first year of primary school, which was aimed to assess the association between age and students cognitive development.Objectives: The study seeks to compare children s development between six and seven years old and verify if they have the same skills related to cognition, comprehension, memory and literacy.Methodology: Cross-sectional study with students attending the first year of primary school at the end of 2011, were 6 or 7 years old and went to preschool in the previous year. We employed specific tests to assess cognition, comprehension, memory and literacy in children.Results: Were evaluated 407 children from the public system (41 classes total) from the city of Porto Alegre, Brazil, which 188 (46.2%) were males and 219 (53.8%) females. The age at the beginning of the school year was 6.3 ± 0.3 years. The time to interview was 8.3 ± 1.0 months.Conclusion: The results indicated no association between age and students performance in the tests that evaluated cognition, memory or comprehension. We found an association between the age at the beginning of the school year and literacy degree at the time students were evaluated. The study show a female advantage in the question cognition. The research show the profile of the groups analyzed in relation to aspects evaluated